Phenyl-β-D-glucopyranoside and Phenyl-β-D-galactopyranoside Dimers: Small Structural Differences but Very Different Interactions - Usabiaga, Imanol; Camiruaga, Ander; Insausti, Aran; Çarçabal, Pierre; Cocinero, Emilio J.; León, Iker; Fernández, José A. (Frontiers in Physics, 2018)
We report a combination of laser spectroscopy in molecular jets and quantum mechanical calculations to characterize the aggregation preferences of phenyl-β-D-glucopyranoside (β-PhGlc) and phenyl-β-D-galactopyranoside (β-PhGal) homodimers. At least two structures of β-PhGlc dimer were found maintaining the same intramolecular interactions of the monomers, but with additional intermolecular interactions between the hydroxyl groups. Several isomers were also found for the dimer of β-PhGal forming extensive hydrogen bond networks between the interacting molecules, of very different shape. All the species found present several CH•••Pi and OH•••Pi interactions that add stability to the aggregates. The results show how even the smallest change in a substituent, from axial to equatorial position, plays a decisive role in the formation of the dimers. These conclusions reinforce the idea that the small structural changes between sugar units are amplified by formation of intra and intermolecular hydrogen bond networks, helping other molecules (proteins, receptors) to easily read the sugar code of glycans.